Structural and Functional Peculiarities of Cold Receptors - Vyazovska, O. V.; Mazalov, V. K.; Kompaniets, A. M. (Problems of Cryobiology and Cryomedicine, 2009)
In this review there are featured the current notions about cold receptors and presented the data about structural and functional properties of temperature transient receptor potential (TRP) channels, being the primary detectors of environmental temperature.